Physical and mechanical properties of spent coffee grounds (SCG) in concrete - Yee, Jia Jun; Khong, Sheh Ching; Tee, Kong Fah; Chin, Siew Choo (Universiti Kebangsaan Malaysia, 2024)
Incorporating waste materials into concrete enhances concrete properties and aligns with sustainable construction concepts. In this study, Spent Coffee Grounds (SCG) were investigated for their potential as an additive material in the cement mortar, to be used as a preliminary investigation for the formation of SCG concrete. SCG were collected from a local traditional Malaysian coffee shop and then undergone oven-drying, grinding and sieving process under controlled laboratory environments to obtain finely grounded SCG powder to be use as additive materials. The study begins with an investigation of the physical and chemical properties of SCG before being applied into cement mortar, through SEM and XRF analysis. Previous literatures have studied the use of SCG as sand substitutes, however, limited studies were conducted in the formation of cement mortar containing SCG additives. Thus, SCG was applied as additives into cement mortar at 6 different percentages of 0%, 1%, 3%, 5%, 7%, and 10%, undergoing 6 different periods of water curing of 7-day, 14-day, 28-day, 35-day, 42-day, and 70-day, tested under compressive strength and flexural strength test. The result of the study shows that under SEM, the SCG tends to form clusters and absorb water, whereas SCG collected for this study contains high carbon content under XRF analysis. The 1 % SCG additive performed the best for both compressive strength and flexural strength outperforming the control mixes. As a conclusion, SCG can be utilized as cement mortar additives when applied at 1%.